Socioeconomic factors, material inequalities, and perceived control in self-rated health: cross-sectional data from seven post-communist countries - Bobak, M; Pikhart, H; Rose, R; Hertzman, C; Marmot, M (Social science & medicine (1982), 2000)
This study examined the association between perceived control and several socioeconomic variables and self-rated health in seven post-communist countries (Russia, Estonia, Lithuania, Latvia, Hungary, Poland, Czech Republic). Questionnaire interviews were used to collect data on self-rated health in the last 12 months, education, marital status, perceived control based on nine questions, and material deprivation based on availability of food, clothing and heating. For each population, two ecological measures of material inequalities were available: an inequality score estimated from the survey data as the distance between the 90th and 10th percentiles of material deprivation, and Gini coefficient from published sources. Data on 5330 men and women aged 20-60 were analysed. Prevalence of poor health (worse than average) varied between 8% in Czechs and 19% in Hungarians. The age-sex-adjusted odds ratio for university vs primary education was 0.36 (0.26-0.49); odds ratios per 1 standard deviation increase in perceived control and in material deprivation were 0.58 (95% CI 0.48-0.69) and 1.51 (1.40-1.63), respectively. The odds ratio for an increase in inequality equivalent to the difference between the most and the least unequal populations was 1.49 (0.88-2.52) using the material inequality score and 1.41 (0.91-2.20) using the Gini coefficient. No indication of an effect of either inequality measure was seen after adjustment for individuals' deprivation or perceived control. The results suggest that, as in western populations, education and material deprivation are strongly related to self-rated health. Perceived control appeared statistically to mediate some of the effects of material deprivation. The non-significant effects of both ecological measures of inequality were eliminated by controlling for individuals' characteristics.
Keywords: Lotyšsko; Poland; Interviews as Topic; Random Allocation; Russia; Cross-Sectional Studies; Estonsko; Socioeconomic Factors; Česká republika; Rusko; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Hungary; sociální podmínky; průřezové studie; Adult; Czech Republic; Polsko; Marital Status; socioekonomické faktory; chudoba; logistické modely; Education; ženské pohlaví; Humans; výchova a vzdělávání; Lithuania; manželský stav; Income; Surveys and Questionnaires; Latvia; odds ratio; náhodné rozdělení; lidé středního věku; rozhovory jako téma; Estonia; příjem; Maďarsko; Health Status; Logistic Models; dospělí; zdravotní stav; Psychosocial Deprivation; Social Conditions; Female; Poverty; psychosociální deprivace; Litva; lidé; Male; Odds Ratio